2009
DOI: 10.1038/nature08519
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Agulhas leakage due to poleward shift of Southern Hemisphere westerlies

Abstract: The transport of warm and salty Indian Ocean waters into the Atlantic Ocean-the Agulhas leakage-has a crucial role in the global oceanic circulation and thus the evolution of future climate. At present these waters provide the main source of heat and salt for the surface branch of the Atlantic meridional overturning circulation (MOC). There is evidence from past glacial-to-interglacial variations in foraminiferal assemblages and model studies that the amount of Agulhas leakage and its corresponding effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
314
2
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(344 citation statements)
references
References 33 publications
22
314
2
6
Order By: Relevance
“…Concurrent to the tropical Atlantic warming, Agulhas leakage-estimated using an established method Biastoch et al 2009)-has increased by about 45% from roughly 13 Sv (1 Sv 5 10 6 m 3 s 21 ) in the early 1960s to roughly 19 Sv in the early 2000s in the hindcast experiment (Fig. 4a).…”
Section: B Effect Of Increased Agulhas Leakage On Temperatures In Thmentioning
confidence: 99%
See 3 more Smart Citations
“…Concurrent to the tropical Atlantic warming, Agulhas leakage-estimated using an established method Biastoch et al 2009)-has increased by about 45% from roughly 13 Sv (1 Sv 5 10 6 m 3 s 21 ) in the early 1960s to roughly 19 Sv in the early 2000s in the hindcast experiment (Fig. 4a).…”
Section: B Effect Of Increased Agulhas Leakage On Temperatures In Thmentioning
confidence: 99%
“…This is consistent with Schmidtko and Johnson (2012), who attributed a warming of the AAIW core between 308 and 208S to increased Agulhas leakage via changes in the southern annular mode (SAM) index, and with McCarthy et al (2011), who showed that a salinification of the AAIW layer has its origin in the Indian Ocean. It is important to note that half of the AAIW immediately west of the Agulhas retroflection has its origin in the Agulhas Current (Biastoch and Böning 2013).…”
Section: B Effect Of Increased Agulhas Leakage On Temperatures In Thmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the warm tropical waters carried by the current stimulate convection of the overlying atmosphere with direct consequences for regional weather systems [Reason and Jagadheesha, 2005]. Second, the shedding of Agulhas rings south of Africa causes buoyancy anomalies in the South Atlantic that stimulate dynamical responses with potential consequences for the Atlantic MOC [Biastoch et al, 2009;Knorr and Lohmann, 2003]. While the significance of these mechanisms is increasingly recognized, their dynamics and sensitivity are not well understood.…”
Section: The Agulhas System and Impactsmentioning
confidence: 99%